2016
DOI: 10.1016/j.gie.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band Imaging International Colorectal Endoscopic Classification to predict polyp histology: REDEFINE study (with videos)

Abstract: The application of the NICE classification to FICE resulted in suboptimal accuracy and only moderate interobserver agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Furthermore, we showed that a training module on SIMPLE classification resulted in an overall NPV of 91.3%. Repici et al [26] recently demonstrated that the application of the NICE classification to the FICE digital chromoendoscopy system resulted in suboptimal accuracy and only moderate inter-observer agreement. In our study, among the three individual NICE criteria, surface and vessel features appeared to be significantly more accurate predictors than the colour criterion alone, which in turn was associated with a poor sensitivity for the prediction of adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that a training module on SIMPLE classification resulted in an overall NPV of 91.3%. Repici et al [26] recently demonstrated that the application of the NICE classification to the FICE digital chromoendoscopy system resulted in suboptimal accuracy and only moderate inter-observer agreement. In our study, among the three individual NICE criteria, surface and vessel features appeared to be significantly more accurate predictors than the colour criterion alone, which in turn was associated with a poor sensitivity for the prediction of adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced endoscopic imaging technologies have made a significant improvement in colorectal polyp characterization. Currently only the NICE classification is used solely for the NBI technology [52] and is not reproducible when different technology is used [53]. In one study blue-light imaging (with or without magnification) was used to create a new classification for distinguishing colorectal polyps (hyperplastic, adenomatous, and invasive malignant lesions) [54].…”
Section: Artificial Intelligence and Blue Light Imaging In Colorectalmentioning
confidence: 99%
“…Recent studies [12, 13] have shown suboptimal diagnostic yields of NICE classification system in predicting pathology of small colorectal polyps; however, we believe the education program we developed in this study will facilitate sufficient and effective training in NBI interpretation in a clinical setting and potentially improve the diagnostic performance of this classification system. A prospective clinical trial on this NBI education program and diagnostic performance is currently underway.…”
Section: Discussionmentioning
confidence: 99%